2021
DOI: 10.1111/josh.13001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Needs of Ontario Educators in Supporting Students With Acquired Brain Injury in the Classroom

Abstract: Background When a child sustains an acquired brain injury (ABI), the impact extends to significant environments in their life, including school. Educator knowledge of ABI can influence a child's success with academic and social reintegration. An assessment of educator ABI knowledge was conducted to determine what information they require to support school reintegration. Methods A mixed‐methods approach included a sampling of educators in a needs assessment survey and workshop. The survey determined levels of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…TeachABI is an online PD module designed to bridge the ABI knowledge gap among primary-school educators in Ontario, Canada (Stevens et al 2021;Saly et al 2023). This 1-h module uses a case study approach, with embedded videos and supplementary resources, to provide educators with an understanding of ABI and strategies to support accessibility and inclusion in the classroom for primary school students with ABI.…”
Section: Teachabi Professional Development Modulementioning
confidence: 99%
“…TeachABI is an online PD module designed to bridge the ABI knowledge gap among primary-school educators in Ontario, Canada (Stevens et al 2021;Saly et al 2023). This 1-h module uses a case study approach, with embedded videos and supplementary resources, to provide educators with an understanding of ABI and strategies to support accessibility and inclusion in the classroom for primary school students with ABI.…”
Section: Teachabi Professional Development Modulementioning
confidence: 99%
“…To address the need for specialized knowledge, an online professional development module, TeachABI , was designed for educators to build knowledge and competency on how to support elementary students with ABI in the classroom. TeachABI was built as an outcome of a needs assessment with Ontario elementary school educators, that identified the importance of resources to support students with ABI [ 15 ]. The needs assessment was critical in understanding what type of training supports and resources educators would like, as well as the nature of information needed to support and build their ABI knowledge [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a gap in training related to mild, moderate, and severe ABI remains. Recently, Stevens and colleagues [ 10 ] confirmed that Ontario educators lack the knowledge and confidence to support students with ABI in the classroom. Ontario educators also reported the need for a course to improve their knowledge and awareness of pediatric ABI.…”
Section: Introductionmentioning
confidence: 99%
“…The problem was identified and examined through a needs assessment workshop conducted with Ontario educators [ 10 ]. Educators confirmed the knowledge gap related to pediatric ABI and identified the need for a standardized, accessible, engaging, and short e-learning program that would help raise awareness and knowledge about pediatric ABI and the unique needs of these students in the classroom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation